Contrasting effects of DNA demethylation on cancer-germline gene expression in breast cancer and leukemia cells - Mikhlid H. Almutairi; Turki M. Alrubie (PLoS ONE, 2025)
Human germline gene expression is normally constrained to the germ cells, responsible for the production of sperm and oocytes. Cancer-germline (CG) genes, a subset of germline genes involved in testis development, are frequently aberrantly activated in cancer cells. The present study investigates the broader hypothesis that epigenetic modifications, specifically DNA methylation, can modulate the expression profiles of several CG genes in cancer and germ cells. Breast cancer (BC), normal breast (NB), and chronic myelogenous leukemia (CML) cell lines were treated with the DNA methyltransferase inhibitor (DNMTi) 5-aza-2’-deoxycytidine for three days. The effects of this treatment on the transcriptional activation of CG genes ( SYCP1 , ADAD1 , SYCE1 , PRSS54 , DMRTC2 , and TEX101 ) were then evaluated. We comprehensively analyzed differential methylation, survival analysis (Kaplan-Meier), correlation (Spearman’s), and pathway enrichment analysis (GO/KEGG) of CG genes (SYCP1, ADAD1, SYCE1, PRSS54, DMRTC2, and TEX101) in BC and leukemia. Treatment with 5-aza-2’-deoxycytidine upregulated CG genes in BC cells but downregulated them in leukemia cells, highlighting tissue-specific epigenetic responses. Differential methylation analysis revealed cancer-specific patterns: ADAD1 was hypermethylated in both malignancies, while PRSS54 was hypomethylated in leukemia. Survival analysis linked SYCE1 and PRSS54 to prolonged survival in BC, whereas TEX101 and SYCP1 correlated with poorer outcomes. Functional enrichment identified ADAD1 and SYCP1 as key players in BC and leukemia pathways, respectively. Meta-analysis validated SYCP1 as a robust biomarker with consistent effect sizes across datasets. Methylation-expression correlations were stronger in tumors, with SYCE1 and DMRTC2 showing inverse relationships in leukemia. These findings demonstrate that the expression of a subset of CG genes is responsive to modulation by hypomethylating drugs in a tissue-specific manner, highlighting their promise as candidates for future investigation in cancer immunotherapy.